Histomorphological spectrum of prostatic lesions: a retrospective analysis of transurethral resection of prostate specimens - Sharma, Anuja; Sharma, Mahima; Gandhi, Shivani; Khajuria, Arvind; Goswami, K. C. (International Journal of Research in Medical Sciences, 2017)
Background: Prostatic diseases like inflammation, benign prostatic hyperplasia and tumors are important causes of mortality and morbidity in males. The incidence of these lesions increases with advancing age. The second most common cancer among males is prostate cancer, next to lung cancer worldwide. Transurethral resection of prostate (TURP) is most frequently preformed surgical procedure in the clinical practice. The purpose of the study is to evaluate histomorphological spectrum of prostate lesions in TURP specimen with focus on premalignant lesions and incidental carcinomas. Methods: The present study includes 245 cases of TURP specimen from January 2015 to December 2016 received in the post graduate department of pathology, ASCOMS and Hospital. H and E stained sections were examined. The relevant clinical details pertaining to age, clinical complaints and microscopic details were analysed and compared with other similar studies. Results: Of the total 245 TURP specimen, 223 (91.02%) were of nodular hyperplasia, 14 (5.71%) were of prostatic intraepithelial neoplasia and 8 (3.26%) cases were malignant. Benign hyperplasia of prostate (BHP) alone accounted for 91.02% of TURP specimen. Less frequent findings were granulomatous prostatitis in 3.70% and atypical adenomatous hyperplasia (1.22%). All the 8 cases of prostate cancer were incidental carcinoma, 5 of which were poorly differentiated and 3 were moderately differentiated adenocarcinoma. Conclusions: The present study showed that non-neoplastic lesions of prostate are more common than neoplastic ones. The most frequently encountered prostatic lesion was BHP, commonly seen in the age group of 61-70 years. The malignant lesions were common among the males of more than 60 years. TURP can be helpful in early identification of premalignant lesions and incidental prostate cancer which can improve the treatment outcome of patients.